Estimating endurance shuttle walk test speed using the six-minute walk test in people with chronic obstructive pulmonary disease - Wootton, S.; Ng, C.; McKeough, Z.; Jenkins, Susan; Hill, Kylie; Alison, J. (Sage Publications Ltd., 2014)
The objective of this study was to derive and validate an equation to estimate the speed for the endurance shuttle walk test (ESWT) using results from the six-minute walk test (6MWT) in patients with chronic obstructive pulmonary disease (COPD). Participants with diagnosed COPD (n=84) performed two incremental shuttle walk tests (LSWTs) and two 6MWTs. ESWT speed was calculated from the ISWT results using the original published method. An equation was derived, which directly related six-minute walk distance (6MWD) to ESWT speed. The derived equation was validated in a different group of people with COPD (n=52). There was a strong correlation between average 6MWD and the calculated ESWT speed (r=0.88, p < 0.001). The ESWT speed (kilometre per hour) was estimated using the following equation: 0.4889 + (0.0083 x 6MWD). The mean difference (± limits of agreement) between ESWT speeds was calculated using the original published method and found to be 0.03 (±0.77) km/hour. When the ISWT is not the test of choice for clinicians, the 6MWT can be used to accurately estimate the speed for the ESWT.